Republic of Equatorial Guinea : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statements by the Executive Director and Authorities of the Republic of Equatorial Guinea. (IMF Staff Country Reports; Country Report ;, 2008)
Equatorial Guinea has recorded one of Africa's fastest growth rates, as its petroleum industry has expanded and strengthened the country's economic and fiscal sustainability. Executive Directors endorsed the National Development Plan to enhance productivity and achieve the MDGs. Directors stressed the need for strong macroeconomic policies and structural measures in safeguarding competitiveness and supported the adoption of a fiscal policy guided by a reduction in the non-oil primary fiscal deficit. They welcomed the creation of a Social Needs Fund and a national Financial Stability Assessment Program (FSAP) to complement the findings of the regional FSAP.